Synthesis and antimicrobial activities of some bridged bis-benzimidazole derivatives - Kucukbay, Hasan; Yilmaz, Ulku; Sireci, Nihat; Onganer, Ayse Nilay (Tubitak Scientific & Technological Research Council Turkey, 2011)
Some bis-benzimidazoles derivatives bearing allyl, crotyl, cinammyl, furfuryl, and thenyl groups were synthesized and their in vitro antimicrobial activity determined against gram-positive and gram-negative bacteria, and fungi by disk-diffusion method. The structures of all new compounds were identified by H-1-NMR, C-13-NMR, and FT-IR spectroscopic techniques and elemental analysis. All the compounds synthesized in this work were examined for their in vitro antimicrobial activities against gram-positive (Staphylococcus aureus and Bacillus megaterium) and gram-negative bacteria (Klebsiella pneumoniae and Escherichia coli), and the yeasts like fungi (Candida globrata and Candida tropicalis). Compared to the reference substances, Cefozine and nystatin, most of the compounds showed high antibacterial and antifungal activities against studied strains with inhibition zones between 8 and 28 mm.
Keywords: Bis-benzimidazole derivatives; antibacterial activity; antifungal activity